The effects of high shear rates on the average hydrodynamic diameter measured in biomimetic HIV Gag virus-like particle dispersions - Wolf, Tobias; Calisan, Kerim Kadir; Stitz, Jörn; Barbe, Stéphan (Frontiers in Bioengineering and Biotechnology, 2024)
HIV Gag virus-like particles (HIV Gag VLPs) are promising HIV vaccine candidates. In literature, they are often described as shear-sensitive particles and authors usually recommend to operate tangential flow filtration (TFF) gently at shear rates below 4000 s -1 to 6000 s -1 . This in turn poses a severe limitation to the performance of TFF-mediated concentration of VLPs, which would be substantially enhanced by working at higher shear rates. To our knowledge studies examining the shear sensitivity of HIV Gag VLPs, providing detailed information and evidence for the fragility of these particles have not been conducted, yet. Thus, we investigated the effect of high shear rates on the colloidal stability of Mosaic VLPs (Mos-VLPs) as relevant examples for HIV Gag VLPs. For this purpose, Mos-VLPs were exposed to different shear rates ranging from 3395 s -1 to 22 365 s -1 for 2 h. The average hydrodynamic diameter (AHD) as well as the polydispersity index (PDI) of the associated particle size distribution were used as stability indicators and measured after the treatment and during storage by means of dynamic light scattering. At high shear rates, we observed an increase in both AHD and PDI during the storage of HIV Mos1.Gag VLPs (bVLP -without envelope proteins) and Mos1.Gag+Mos2S.Env VLPs (eVLP -with envelope proteins). eVLPs exhibited higher colloidal stability than bVLPs and we discuss the potential stabilizing role of envelope proteins. We finally demonstrated that the dispersion medium also has a considerable impact on the stability of Mos-VLPs.